Desenvolvimento de métodos microbiológicos para doseamento de gramicidina matéria-prima - Ana Gabriela Reis Solano (2008)
Gramicidin is a linear N-formylated pentadecapeptide-ethanolamide complex and active against Gram-positive organisms. It was first isolated from Bacillus brevis. The turbidimetric method is described in the United States Pharmacopoeia and British Pharmacopoeia to analyze gramicidin. Moreover, the results obtained in this assay were no satisfactory. The diffusion method is no described to analyze gramicidin. The present study reports the development and validation of the microbiological assays, applying the cylinder-plate and tube-assay, for the quantitation of gramicidin in raw material. The cylinder-plate method was developed using nutrient agar and a strain of Kocuria rhizophila ATCC 9341 as the test organism. The 3x3 and 5x1 experimental designs were applied. The validation of the method demonstrated that the method was precise (intra-assay: R.S.D. 0.81 3x3; 1.90 5x1; inter-assay: R.S.D. 1.35 3x3; 2.64 5x1), accurate (the 95% tolerance interval obtained was totally included within the acceptance limits) and selective. The calibration curve was linear from 5.00 to 25.3 g/ml. The detection, lower and upper quantification limit were 2.00; 5.00 and 25.3 g/ml, respectively. The F-test indicated that there is no significant difference between the two designs applied in the diffusion assay. The turbidimetric method was developed using GCLT broth (formulated in the laboratory) and Enterococcus hirae ATCC 10541 as the test organism. Also the 3x3 and 5x1 experimental designs were applied. The calibration curve was linear from 0.08 to 0.88 g/ml. The results obtained in this assay were precise (intra-assay: R.S.D. 0.18 3x3; 2.32 5x1; inter-assay: R.S.D. 0.69 3x3; 2.47 5x1) and accurate (the 95% tolerance interval obtained was totally included within the acceptance limits). The detection, lower and upper quantitation limit were 0.06; 0.08 and 0.88 g/ml, respectively. When turbidimetric assay was used, the 3x3 design was more precise than 5x1. The F-test indicated that there is no significant difference between the precision of two methods (p>0,05).